Knowing what you don’t know. Lessons learned from managing the logistics of mine closure - Rogers, T; Botha, Z (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
Lessons learned from managing the logistics of mine closure. The process of mine closure is complex and requires extensive analysis, planning and management to ensure efficient and safe completion that meets the needs of stakeholders. The mine asset will have played a key role in the establishment of crucial infrastructure and supply chains, which local communities may rely on as a source of major revenue and jobs. Decommissioning and rehabilitation of a physical mine site is challenging, and our experience suggests there are many inhibitors to success. Mines are often located in geographically challenging locations, creating unique logistics issues, a mixed regulatory environment and reduced pool of available contractors capable of delivering the decommissioning and reclamation requirements. Years of ongoing upgrades and modification in addition to expansion at the mine means a single source of accurate mine asset information may simply not exist. This creates challenges for mine closure teams resulting in expensive and time-consuming asset mapping to provide a single version of the truth. This paper presents a critical review of the planning and delivery of logistics management during mine closure. It will explore the challenges, potential risks and provide lessons learned based on our experience of mine closure logistics and materials management. The operation of mine closure can be improved through initiatives such as the implementation of new technologies that capture, store, retrieve and distribute important physical records to support those making decisions about disposal. This digitization initiative plays a critical role in ensuring compliance with legal and regulatory requirements, as well as maintaining efficiency and safety as the mine closes. Given the complex and high-risk nature of the mining industry, it is essential to have efficient processes in place to ensure that all relevant stakeholders have access to relevant documents such as permits, licenses, contracts alongside the ability to sign off decisions. The paper will support mining companies to improve resilience in mine closure and to remove excess risk associated with logistics project management and execution.
Keywords: Mine closure logistics; logistics; digitization